Kearny's march : the epic creation of the American West, 1846-1847 - Groom, Winston, 1944-2020- (Alfred A. Knopf, 2011)
In June 1846, General Stephen Watts Kearny rode out of Fort Leavenworth, Kansas, with two thousand soldiers, bound for California. The nation was hell-bent on expansion: James K. Polk had lately won the presidency by threatening England over the borders in Oregon, while Congress had just voted, in defiance of the Mexican government, to annex Texas. After Mexico declared war on the United States, Kearny's Army of the West was sent out, carrying orders to occupy Mexican territory. When his expedition ended a year later, the country had doubled in size and now stretched from the Atlantic to the Pacific.